Metoclopramide as a prokinetic agent for diabetic gastroparesis: revisiting the risk of Parkinsonism - Chien-Hsu Lai; Yi-Chun Yeh; Yen-Yu Chen (SAGE Publishing, 2019)
Background: Metoclopramide is used to relieve gastrointestinal symptoms, however, it could cause adverse reactions of motor disorders. The aim of this study was to investigate whether metoclopramide treatment has a duration-response or dose-response effect and to estimate the risk of developing Parkinsonism following different and specific durations of treatment. Methods: A cohort study of newly diagnosed type 2 diabetes mellitus in 45- to 79-year-old patients, between 1999 and 2008, was selected using the Longitudinal Health Insurance Database 2005. A nested case-control study was conducted in the diabetes cohort in which all incident cases of Parkinsonism were identified. We randomly matched each case with up to 10 controls from the risk set. Conditional logistic regression was utilized to estimate odds ratio of Parkinsonism associated with metoclopramide use. Results: A total of 34,685 patients with diabetes were assembled as the cohort, and 541 incident Parkinsonism cases were identified. There were duration-response and dose-response effects on the risk of developing Parkinsonism. Compared with never-use patients, the adjusted odds ratios (ORs) of continuing therapy for 0-1 month, 1-2 months, 2-3 months, 3-5 months, and more than 5 months were 1.17 [95% confidence interval (CI) 0.93-1.45], 1.44 (95% CI 1.04-2.00), 1.74 (95% CI 1.14-2.65), 1.90 (95% CI 1.23-2.93), and 2.17 (95% CI 1.50-3.12), respectively. Conclusions: With metoclopramide treatment, regardless of less or more than 3 months of use, the risk of developing Parkinsonism in patients with newly diagnosed diabetes escalated with the duration of therapy. Therefore, we recommend close monitoring for the development of Parkinsonism in patients treated with metoclopramide, particularly (but not limited to) those with prolonged exposure.